Optimal Design of a Secondary Optical Element for a Noncoplanar Two-Reflector Solar Concentrator - Yi-Cheng Chen; Chia-Chi You (International Journal of Photoenergy)
This paper presents the results of a parametric design process used to achieve an optimal secondary optical element (SOE) in a noncoplanar solar concentrator composed of two reflectors. The noncoplanar solar concentrator comprises a primary parabolic mirror (M1) and a secondary hyperbolic mirror (M2). The optical performance (i.e., acceptance angle, optical efficiency, and irradiance distribution) of concentrators with various SOEs was compared using ray-tracing simulation. The parametric design process for the SOE was divided into two phases, and an optimal SOE was obtained. The sensitivity to assembly errors of the solar concentrator when using the optimal SOE was studied and the findings are discussed.